ASPEK PERPAJAKAN PADA PERUSAHAAN YANG MEMANFAATKAN MARKETPLACE DALAM KEGIATAN USAHA: STUDI KASUS PADA CV X - Saktiana Rizki Endiramurti; Grace Silla Devinta Putri; Rozie, Fahrur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the taxation aspects of CV X as a company that utilizes marketplace in business activities in Indonesia. CV X is a micro company engaged in the retail trade of clothing. The method used in this study is a case study with analysis of CV X's financial and tax data during 2024. The results of the study indicate that CV X has carried out its tax obligations according to the provisions, including payment of Final Income Tax Article 4(2) MSMEs, Final Income Tax Article 4(2) Rent, and Income Tax Article 21, but still faces challenges in recording complex transactions, as well as the time difference between receipt of goods and disbursement of funds, which has the potential to cause inaccuracies in revenue recognition and tax reporting. It can be concluded that CV X's tax compliance is quite good, but it needs to improve the bookkeeping system and tax socialization to overcome existing challenges.